THU0046 A PIPELINE TO STUDY ANTIGEN-SPECIFIC CD4+ T CELLS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Kumar, R.; Yoosuf, N.; Gerstner, C.; Turcinov, S.; Chemin, K.; Malmström, V.
Abstract : Background: Autoimmunity to citrullinated autoantigens forms a critical component of disease pathogenesis in rheumatoid arthritis (RA). Presence of anti-citrullinated protein antibodies (ACPAs) in patients has high diagnostic value. Recently, several citrullinated antigen specific CD4+T cells have been described. However, detailed studies of their T-cell receptor usage and in-vivo profile suffer from the disadvantage that these cells are present at very low frequencies. In this context, we here present a pipeline for TCR repertoire analysis of antigen-specific CD4+T cells from RA patients, including both citrulline and influenza (control) specificities using in-vitro peptide challenge induced-cell expansion. Objectives: To enable studies of the T cell repertoire of citrullinated antigen-specific CD4+T cells in rheumatoid arthritis Methods: Peripheral blood mononuclear cells (PBMCs) (n=7) and synovial fluid mononuclear cells (SFMCs) (n=5) from HLA-DR*0401-postive RA patients were cultured in the presence of citrullinated Tenascin C peptide cocktails or influenza peptides (positive control). Citrulline reactive cells were further supplemented with recombinant human IL-15 and IL-7 on day 2. All cultures were replenished with fresh medium on day 6 and rIL-2 was added every 2 days from then. Assessment of proportion of peptide-HLA-tetramer positive cells was performed using flow cytometry whereby individual antigen-specific CD4+T cells were sorted into 96-well plates containing cell lysis buffer, followed by PCR-based alpha/beta TCR sequencing. TCR sequencing data was demultiplexed and aligned for TCR gene usage using MiXCR. Some tetramer positive cells were sorted into complete medium containing human IL-2 and PHA for expansion of antigen-specific cells. Cells were supplemented with irradiated allogenic PBMCs (30 times number of antigen specific cells). Clones of antigen specific CD4+T cells were further subjected to tetramer staining to confirm expansion of cells. Results: As evidenced by increase in frequency of tetramer positive CD4+T cells, in vitro peptide stimulation resulted in expansion of both influenza specific (Fig. 1a ) and citrullinated antigen specific (Fig. 1b ) CD4+T cells. Polyclonal in-vitro expansion of tenascin C tetramer positive sorted cells followed by tetramer staining further confirmed antigen specificity and enrichment for antigen specific CD4+T cells after polyclonal stimulation (Fig.1c). TCR repertoire analysis in PB and SF dataset from the first patient showed clonal expansion of influenza specific cells in both sites. Synovial fluid had more diversity of expanding clones as compared to paired PB, with few expanded clones being shared among SF and PB. We observed a more diverse TCR repertoire in citrulline specific CD4+T cells. We also observed sharing of TCR alpha chains among different citrulline specific CD4+T cell clones. Conclusion: This method provides a highly suitable approach for investigating TCR specificities of antigen specific CD4+T cells under conditions of low cell yields. Building on this dataset will allow us to assess specific features of TCR usage of autoreactive T cells in RA. PBMCs were cultured in presence of (a) influenza (HA, MP54) and (b) citrullinated tenascin peptides. The proportion of antigen specific CD4+T cells was assessed using HLA-class II tetramer staining. We observed an increase in frequency of (a) Infleunza specific cells (red dots in upper left and lower right quadrants) and (b) citrullinated tenascin C specific cells (red dots in lower right quadrant), at day 13 post culture as compared to day 3. (c) Sorting of citrullinated tenascin specific CD4+T cells, followed by PHA expansion resulted in visible increase in proportion of citrullinated tenascin specific CD4+T cells. Disclosure of Interests: Ravi kumar: None declared, Niyaz Yoosuf: None declared, Christina Gerstner: None declared, Sara Turcinov: None declared, Karine Chemin: None declared, Vivianne Malmström Grant/research support from: VM has had research grants from Janssen Pharmaceutica